2022
DOI: 10.3390/membranes12050446
|View full text |Cite
|
Sign up to set email alerts
|

All-Solid-State Potentiometric Platforms Modified with a Multi-Walled Carbon Nanotubes for Fluoxetine Determination

Abstract: Novel cost-effective screen-printed potentiometric platforms for simple, fast, and accurate assessment of Fluoxetine (FLX) were designed and characterized. The potentiometric platforms integrate both the FLX sensor and the reference Ag/AgCl electrode. The sensors were based on the use of 4′-nitrobenzo-15-crown-5 (ionophore I), dibenzo-18-crown-6 (ionophore II), and 2-hydroxypropyl-β-cyclodextrin (2-HP-β-CD) (ionophore III) as neutral carriers within a plasticized PVC matrix. Multiwalled carbon nanotubes (MWCNT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The reference electrode should maintain a stable potential, to avoid drifting during time that can strongly modify the calibration curve of the device. This stability is often achieved by covering the electrode made of a stable and inert metal with a protecting porous membrane that freely enables the exchange of ions, usually made of polyvinyl butyral (PVB) as highlighted in most of the literature [26]- [34].…”
Section: Working Principle Of All-solid-state Ises (Ass-ises)mentioning
confidence: 99%
“…The reference electrode should maintain a stable potential, to avoid drifting during time that can strongly modify the calibration curve of the device. This stability is often achieved by covering the electrode made of a stable and inert metal with a protecting porous membrane that freely enables the exchange of ions, usually made of polyvinyl butyral (PVB) as highlighted in most of the literature [26]- [34].…”
Section: Working Principle Of All-solid-state Ises (Ass-ises)mentioning
confidence: 99%
“…The Abd-Rabboh group [ 92 ] showed that screen-printed potentiometric platforms modified with polymers and MWCNTs are capable of detecting trace amounts of fluoxetine, where MWCNTs provide a high potential stability in the sensors compared to the low potential stability in unmodified sensors. They deemed the electrode polarizable, avoiding the ability to buffer any random tiny charge noise [ 92 ].…”
Section: Carbon–polymer Composite-based Modification Of Electrode Sur...mentioning
confidence: 99%
“…For simple and valuable measurement purposes, screen-printed based on ISEs has great attention due to their sensitivity, selectivity, and potential stability 10 . Recently, screen-printed SC- ISEs integrated with polymeric and /or nanomaterials layers have a straightforward approach to monitoring different analytes 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%